-(7x-2)+3x=3(-2x-6)

Simple and best practice solution for -(7x-2)+3x=3(-2x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(7x-2)+3x=3(-2x-6) equation:



-(7x-2)+3x=3(-2x-6)
We move all terms to the left:
-(7x-2)+3x-(3(-2x-6))=0
We add all the numbers together, and all the variables
3x-(7x-2)-(3(-2x-6))=0
We get rid of parentheses
3x-7x-(3(-2x-6))+2=0
We calculate terms in parentheses: -(3(-2x-6)), so:
3(-2x-6)
We multiply parentheses
-6x-18
Back to the equation:
-(-6x-18)
We add all the numbers together, and all the variables
-4x-(-6x-18)+2=0
We get rid of parentheses
-4x+6x+18+2=0
We add all the numbers together, and all the variables
2x+20=0
We move all terms containing x to the left, all other terms to the right
2x=-20
x=-20/2
x=-10

See similar equations:

| 6(8+2x)=3+3(1+3x) | | 5/2(2-3/4x)-3/2=12x+8/5 | | 11=q/3+6 | | 3(f-86)=15 | | 6(5-5x)-7(1+5x)=-42 | | 15+5y=1200 | | 36+x-5=9x-2+3x | | 13a-11a+a-2a=19 | | .5t-4=t-0.8 | | 35=5(1-6x)+4(-8-8x) | | -2+3t=13 | | 4x-8+4=0 | | -6v+-20=52 | | 7(-7x-8)-2(4x-2)=-52 | | 5+x=19+3x | | 8g-5g-3g+2g+g=18 | | -4-7(2+4x)=-7x-39 | | 60=6(p+5) | | p+2p/3+p/2=234 | | 17+9c=-7+3c | | t+t+t-t=16 | | -7-1(x-5)=6-2x | | 12x+28/12=4+2x/25 | | 9(m+9)=63 | | 6(4+5x)=2x-4 | | 0.2=x/0.8 | | 9(m+9)=3 | | 6j-6j+3j-2j+J=10 | | -7(-2+7x)=-38+3x | | -5(x+2)=-10(x+1/5) | | -x-2=10-7x | | 10-4x=5x-26 |

Equations solver categories